Prinsip Kebenaran dalam Pemberitaan Virus Corona di Media Kompas.com - Rakha Fauzan Hawadi; Atie Rachmiatie (UNISBA Press, 2022)
Abstract. This research is motivated by the massive coverage of the corona virus in online media, almost all online mass media make health issues related to the corona virus the prima donna of news. However, in practice many mass media are the principles of truth in journalism and prioritize speed in delivering news. Kompas.com is one of the online media that intensively spreads information related to the corona virus. From some of the news that he published, it was necessary to question his responsibility and the principles of truth he applied. According to Bill Kovach truth in journalism is absolute truth, but functional truth. Therefore, the purpose of this study is to find out about the principle of truth in the corona virus news text in the online media Kompas.com. Also to find out the principle of truth in the practice of discourse in reporting the corona virus in the online media Kompas.com. Finally, to find out socio-cultural practices in reporting the corona virus on Kompas.com online media. The methodology used is qualitative with Norman Fairclough's Critical Discourse Analysis approach. The results of this study show; (1) Kompas Online presents the truth that is not deep enough and positions itself as a transmitter and receiver of information. (2) The discourse of truth that is displayed does not represent the vision of Kompas Online with the lack of balance in the news and the tendency for speed. (3) The factors of the pandemic situation and the information needs that pushed Kompas Online to become one of the factors in the news about the current corona virus, on the other hand the culture of conformity of the Indonesian people also influenced Kompas Online in its reporting so that the discourse presented to the public seemed short and lacked depth. Abstrak. Penelitian ini dilatarbelakangi oleh masifnya pemberitaan virus corona di media online, hampir seluruh media massa online menjadikan isu kesehatan terkait virus corona menjadi primadona pemberitaannya. Namun dalam pelaksanaannya banyak media massa yang kerap mengabaikan prinsip kebenaran dalam jurnalisme dan mengutamakan kecepatan dalam menyampaikan berita. Kompas.com merupakan salah satu media online yang secara intens mengbarkan informasi terkait virus corona. Dari beberapa pemberitaan yang dimuatnya, perlu dipertanyakan kredibilitas serta prinsip kebenaran yang diterapkannya. Menurut Bill Kovach kebenaran dalam jurnalisme bukanlah kebenaran yang mutlak, melainkan kebenaran yang fungsional. Maka dari itu, tujuan penelitian ini adalah untuk mengetahui tentang prinsip kebenaran pada teks pemberitaan virus corona di media online Kompas.com. Juga untuk mengetahui prinsip kebenaran pada praktik wacana dalam pemberitaan virus corona di media online Kompas.com. Terakhir untuk mengetahui praktik sosial budaya dalam pemberitaan virus corona di media online Kompas.com. Metodologi yang digunakan adalah kualitatif dengan pendekatan Analisis Wacana Kritis Norman Fairclough. Hasil dari penelitian ini menunjukan; (1) Kompas Online menampilkan wacana kebenaran yang kurang mendalam serta memposisikan dirinya sebatas penyampai dan penerima informasi. (2) Wacana kebenaran yang ditampilkan tidak merepresentasikan visi dari Kompas Online dengan kurang berimbangnye berita dan kecenderungan pada kecepatan. (3) Faktor situasi pandemi dan kebutuhan informasi mendorong Kompas Online menjadi salah satu faktor dari pemberitaan mengenai virus corona saat ini, di sisi lain budaya komformitas masyarakat Indonesia turut memengaruhi Kompas Online dalam pemberitaannya sehingga wacana yang ditampilkan kepada masyarakat terkesan singkat dan kurang mendalam.